Evaluating a public productivity policy from the perspective of implementers (Desenvolvimento em Questão, 2026)
Public productivity policies have assumed a central role in contemporary regional development strategies by linking economic competitiveness, innovation, and sustainability in territorial contexts marked by productive and institutional heterogeneity. Despite their growing relevance, the effectiveness of these policies depends to a large extent on implementation processes, in which formal guidelines are translated and adapted to local organizational realities. In this context, this study analyzes the outcomes of the DF Mais Produtivo Program from the perspective of its implementers. The data were obtained from 26 questionnaires answered by the program's technical consultants and analyzed using Factor Analysis and Correspondence Analysis. The results indicate higher perceived impacts in the dimensions of productivity and business owners’ engagement, intermediate impacts associated with innovation, image, and consultants’ satisfaction, and relatively lower impacts in the dimensions of sustainability and employees’ engagement. The analysis shows that program effectiveness is strongly associated with technical mediation, organizational learning, and the adaptive capacity of implementers. It is concluded that evaluating productivity policies from the implementation arena contributes to a more comprehensive understanding of the institutional mechanisms that underpin regional development, reinforcing the strategic role of intermediaries in translating policies into concrete outcomes.
Keywords: Public Policy Implementation; Regional Development; Factor Analysis; Correspondence Analysis